Pietra ollare artefacts from Červar Porat (Istria, Croatia) - Tibljaš, Darko (Array, 2008)
During archaeological excavations of Roman villa rustica in Červar-Porat located close to the town Poreč (Istria peninsula, W Croatia) which were performed in the 1976-1980 period, among other Late Antique period fragments (glass, metal, ceramics), fourteen peculiar stone vessel fragments, showing tracks of the manufacturing by means of lathe, were discovered. Two of these vessel fragments were recently investigated in more detail by mineralogical methods. The first one is greenish-grey in colour. The other one has dark greenish-grey colour on broken surface, while it is brown on outer and inner vessel surfaces, with distinctive bronze coloured flakes at several parts. X-ray powder diffraction method analysis revealed that the only constituent of the first fragment is the chlorite group mineral. Mineral composition together with visible schistosity indicates that source material was chlorite-schist, a low-grade metamorphic rock. Such material is one of different lithologies being enclosed by Italian term pietra ollare and German Lavez. The fact that XRD pattern of other fragment was similar to the XRD pattern recorded on the material from the first fragment after heating to 1100°C indicate that the other vessel was most probably used for cooking, and during that process it was exposed to elevated temperatures. Vessels made by analogous processes from similar materials have already been found at several localities along the Croatian Adriatic coast but no systematic mineralogical study on this kind of material was performed so far. Adequate raw materials can not be found in Istria and its nearest surroundings therefore import of this kind of vessels should be presumed. Most probably the material originates from Alpine-Dinaridic realm.